Dance and drama in Uganda the pearl of Africa - Battye, Susan; Ntangaare, Mirembe; Allan, Ian (Auckland, N.Z. : Drama Magic : distributed by Contemporary Arts Media, 2005)
Looking at Dance and Drama in context is a key aim of New Zealand and Australian Arts Curricula. Students can see for themselves how people live in a part of the world which they know little about, but which has much to offer. They will discover the power of dance and drama to transform lives and explore the many opportunities to make contact with the groups and individuals involved in this work
Title from title screen
An interactive e-book.'
System requirements: PC running Microsoft Windows 98/2000/XP or an Apple Macintosh running Mac OS9/OSX; web browser (such as Microsoft Internet Explorer 5.0+ or Mozilla 5.0/FireFox 1.0+) with Javascript enabled; Apple Quicktime Player; Adobe Acrobat Reader 4.0+
Keywords: Dance -- Uganda -- Interactive multimedia; Musical instruments -- Uganda -- Interactive multimedia; Theater -- Uganda -- Interactive multimedia